(3GdSdhc deYQaI Ohd Gdedhcs - (3Jbj GdOjf CMeO Hf Ydj Hf YHO GdbGOQ GdebQjRj GdeUQj,J (B854 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdCHhGH ajg (B: (3PcQ eG cGf Ydjg GdcGaI bHd bjGe edI GdESdGe s
(3BNQgG (B:s
(3BNQg eHJhQ hBNQ eG ajg aXgQJ WhGdY GdJJQ afhOi YfO Pdc ai GdYSGcQ Cf CQehG GdQeGM hGYJeOhG Ydi GdSjha hGdOHhS , aGdbhG QeGMge cdge Ydi s
(3GfXQ GjVG Qbe (B284 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B233 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs